Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

Mussel-inspired surface modification for high-rate and effectively complex wastewater systems purification - Minrui Zhan; Xi Zhang; Rong Liu; Manman Zhao; Wenkai Li; Huiyu Yang; Jiehao Du; Wei Chen; Shaojin Gu; Xin Liu; Bin Shang (Desalination, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A nitrogen-rich covalent organic framework with high conductivity for high specific capacity Li-ion battery cathode - Xiaoning Zhan; Yucheng Jin; Rong Jiang; Dongdong Qi; Xiya Yang; Qi Zhang; Qingmei Xu; Zhixin Liu; Liancong Yue; Hailong Wang (Science Bulletin, 2026)

One stone, two birds: Preparation of nutritionally fortified and easy-to-swallow 3D printed pea protein gel based on high internal phase emulsions - Wei Liang; Junhong Xie; Qiannan Zhao; Chenghong Jiang; Xiaofeng Zhan; Mingrong Chen; Lu Zhang; Chuan Li; Jianhua Rong; Yang Hu (Food Hydrocolloids, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

Glycine Drives IMP Production in Hybrid Bream (Megalobrama Amblycephala ♀ × Culter Alburnus ♂) Via Concerted Action: Activating glycyl-tRNA Synthetase and Fueling the Pentose Phosphate Pathway - Zhehua Xu; Weiting Zhang; Ruijie Zhan; Jiefan Zhou; Man Chen; Yonghua Zhou; Fufa Qu; Rong Zhou; Shaochun Liu; Shenping Cao; Jianzhou Tang; Zhen Liu (Marine Biotechnology, 2026)

Dual regulation of surface electronegativity and interlayer structural feature in fluorinated COFs for efficient gold recovery - Xiaoning Zhan; Yucheng Jin; Bin Han; Dongdong Qi; Chunli Li; Rong Jiang; Xiaonan Pang; Guoqing Xu; Mingyue Wang; Qi Zhang; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

Introduce multivariate two-dimensional information to establish a data-driven volume estimation model for complex microplastic fibers - Zhan-Ao Zhang; Rong Zhang; Rui Gan; Runqi Liu; Xuxiang Zhang; Yan Zhang (Science of The Total Environment, 2025)

The first set of Silurian marine red beds in South China: Spatiotemporal distribution, diachronism and paleogeographic significance - Xiaole Zhang; Jiayu Rong; Peng Tang; Renbin Zhan; Yi Wang; Zhongyang Chen; Ruiwen Zong; Bing Huang; Xin Wei (Science China Earth Sciences, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Self-powered and self-sensing water meter using contact-separation triboelectric nanogenerator with harvesting local head loss - Da-Qi Cao; Xiao-Dan Liu; Rong-Kun Fang; Guri Yihuo; Yun-Feng Wu; Zhan-Gao Huang; Wen-Yu Zhang; Xiangyu Chen; Xiao-Di Hao (Journal of Water Process Engineering, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Experimental and numerical study of light, fragile vent covers under vented gas explosions - Baicheng Zhou; Xudong Zhi; Yuhuan Song; Zhan Li; Feng Fan; Rong Zhang (Engineering Structures, 2025)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Synergistic adsorption and degradation of sulfonylurea herbicides by biochar-supported nano zero-valent iron composites in in-situ soil remediation - Wenwen Xie; Cheng Peng; Anqi Chen; Haoran Wang; Mabinty Sarah Tholley; Rong Qian; Sinan Lu; Wei Zhang; Xiuping Zhan (Chemical Engineering Journal, 2024)

Modeling of activated carbon and multi-scale molecular simulation of its water vapor adsorption: A review - Zhongfan Mo; Ming Li; Shengnan Sun; Rong Zhu; Danya Zhan; Aimin Li; Yinning Li; Ying Zhang; Qiongfen Yu (Journal of Environmental Chemical Engineering, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Fibroblast-localized lncRNA CFIRL promotes cardiac fibrosis and dysfunction in dilated cardiomyopathy - Shuai Yuan; Xudong Zhang; Jiabing Zhan; Rong Xie; Jiahui Fan; Beibei Dai; Yanru Zhao; Zhongwei Yin; Qian Liu; Dao Wen Wang; Huaping Li; Chen Chen (Science China Life Sciences, 2024)

Overview of the recent advances in porcine epidemic diarrhea vaccines - Miao-Zhan Wei; Lan Chen; Rong Zhang; Ze Chen; Yan-Juan Shen; Bi-Jun Zhou; Kai-Gong Wang; Chun-Lan Shan; Er-Peng Zhu; Zhen-Tao Cheng (The Veterinary Journal, 2024)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Detrital zircon age signatures of the basal Cambrian sandstone unit in North China: implications for drainage divides during global Sauk transgression and separation from Gondwanaland - Rong-Hao Wei; Liang Duan; Xingliang Zhang; Qing-Ren Meng; Rong-Ruo Zhan; Chu-Xuan Ma; Jing Xu; Yi Shi; Xiao-Yin Zhang (International Geology Review, 2023)

Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Leiqiang Gong; Huiying Zhan; et al. (Science of The Total Environment, 2023)

Electromagnetic monitoring with local mesh for time-lapse monitoring of hydraulic fracturing - Zihao Zhang; Jianxin Liu; Rongwen Guo; Kouao Laurent Kouadio; Shaoquan Zhan; Aiyong Li; Rong Liu (Journal of Applied Geophysics, 2023)

Origin of clay in granite intrusive contact zone and its influence on tunnel deformation and instability - Guo-Hua Zhang; Bo-Wen Zhang; Fei Tan; Zhong-Hou Liu; Jun-Peng Zou; Zhong-Zhi Xie; Jin-Quan Wu; Zhi-Ping Lin; Zhan-Rong Zhang (Engineering Geology, 2023)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Reasonable application range of flocculation–solidification combined method in treatment of hydraulically dredged mud slurry - Rong-Jun Zhang; Zhi-Hao Xu; Jun-Jie Zheng; Lin-Wei Tu; Zhan-fang Huang (Marine Georesources & Geotechnology, 2022)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

A Density-Changing Centrifugation Method for Efficient Separation of Free Drugs from Drug-Loaded Particulate Delivery Systems - Lu Han; Hongyan Zhan; Xun Sun; Zhi-Rong Zhang; Li Deng (The AAPS Journal, 2019)

Silurian integrative stratigraphy and timescale of China - Jiayu Rong; Yi Wang; Renbin Zhan; Junxuan Fan; Bing Huang; Peng Tang; Yue Li; Xiaole Zhang; Rongchang Wu; Guangxu Wang; Xin Wei (Science China Earth Sciences, 2019)

Origin and genetic family of Huhehu oil in the Hailar Basin, northeast China - Yao-Ping Wang; Fan Zhang; Yan-Rong Zou; Zhao-Wen Zhan; Yulan Cai (Acta Geochimica, 2018)

Population transcriptomes reveal synergistic responses of DNA polymorphism and RNA expression to extreme environments on the Qinghai–Tibetan Plateau in a predatory bird - Shengkai Pan; Tongzuo Zhang; Zhengqin Rong; Li Hu; Zhongru Gu; Qi Wu; Shanshan Dong; Qiong Liu; Zhenzhen Lin; Lucia Deutschova; Xinhai Li; Andrew Dixon; et al. (Molecular Ecology, 2017)
Low oxygen and temperature pose key physiological challenges for endotherms living on the Qinghai–Tibetan Plateau ( QTP ). Molecular adaptations to high‐altitude living have been detected in the genomes of Tibetans, their domesticated animals and a few wild species, but the contribution of transcriptional variation to altitudinal adaptation remains to be determined. Here we studied a top QTP predator, the saker falcon, and analysed how the transcriptome has become modified to cope with the stresses of hypoxia and hypothermia. Using a hierarchical design to study saker populations inhabiting grassland, steppe/desert and highland across Eurasia, we found that the QTP population is already distinct despite having colonized the Plateau cDNA level, but of only seventeen genes identified, three function in hypoxia and four in immune response. Our results show a significant role for RNA transcription: 50% of upregulated transcription factors were related to hypoxia responses, differentiated modules were significantly enriched for oxygen transport, and importantly, divergent EPAS 1 functional variants with a refined co‐expression network were identified. Conservative gene expression and relaxed immune gene variation may further reflect adaptation to hypothermia. Our results exemplify synergistic responses between DNA polymorphism and RNA expression diversity in coping with common stresses, underpinning the successful rapid colonization of a top predator onto the QTP . Importantly, molecular mechanisms underpinning highland adaptation involve relatively few genes, but are nonetheless more complex than previously thought and involve fine‐tuned transcriptional responses and genomic adaptation.

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

Perceptual quality assessment of SAR image compression - Anzhou Hu; Rong Zhang; Dong Yin; Yuan Chen; Xin Zhan (International Journal of Remote Sensing, 2013)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Cloning and functions analysis of a pyruvate dehydrogenase kinase in Brassica napus - Rong-Jun Li; Zhi-Yong Hu; Hua-Shan Zhang; Gao-Miao Zhan; Han-Zhong Wang; Wei Hua (Plant Cell Reports, 2011)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Characterizing and estimating rice brown spot disease severity using stepwise regression, principal component regression and partial least-square regression - Zhan-yu Liu; Jing-feng Huang; Jing-jing Shi; Rong-xiang Tao; Wan Zhou; Li-li Zhang (Journal of Zhejiang University-SCIENCE B, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)